Nanotechnology and Primary Hemostasis: Differential Effects of Nanoparticles on Platelet Responses - Vilos-Ortiz, C (Elsevier Inc., 2018)
Despite the numerous advantages offered by diverse platforms based on nanomedicine, several nanomaterials have shown significant cell toxicity that could induce chronic adverse effects on human health. Blood compatibility is one of the leading factors to consider for the design and development of nanosystems as therapeutics. Aforementioned is because systemic circulation is the gateway for most nano-drug therapeutic systems and its interactions with the blood components such as platelets could influence the maintenance of hemostasis and thrombus formation. Unfortunately, the thrombotoxicity of some nanomaterials regarding the activation/inhibition of platelets limits their biomedical applications. Additionally, the critical factors that drive those effects on platelet function are still not entirely elucidated. In this work, we describe the effect of different nanomaterials on the platelet function, its action mechanisms, and future potential as nanotherapeutics. © 2017 Elsevier Inc.